Design and Implementation of an Efficiently Managed Wireless Internet Service Providing (WISP) System (Al-Mansour Journal, 2023)
In this paper, a comprehensive study to the structure, behavior and management of a Wireless Internet Service Provider (WISP) system is presented. The structure of the system is investigated and the importance of the different parts of the system is clearly determined. Also, WISP system was subjected to different tests such as load test, user behavior and page response time. The design methodology and data given here could be used by the planners, developers and researchers of such a sophisticated network field.